Peranan Bahasa Inggris terhadap Komunikasi Efektif bagi Wisatawan Mancanegara di Museum Negeri Provinsi Sumatera Utara - Susanna Silvia Sembiring (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
The North Sumatra Provincial Museum, as one of Indonesia’s leading cultural tourism destinations, encounters challenges in facilitating effective communication for international visitors. Despite housing extensive collections of Batak, Malay, and Nias artifacts that attract thousands of tourists annually, the limited use of English often constrains intercultural interaction. This study aims to examine the role of English as a medium of communication in enhancing foreign visitors’ experiences, identify linguistic barriers, and propose improvement strategies. Employing a descriptive qualitative case study design, data were collected through in-depth interviews and participant observation involving 50 international tourists (aged 18–65) from Europe, the Americas, and Asia who visited between January and March 2023. Data were analyzed thematically using NVivo software, supported by museum documents such as brochures and the website. Findings revealed that English proficiency among staff and the availability of English-language materials increased visitor satisfaction by 75%. However, communication barriers included the strong local accent (reported by 40% of respondents) and the lack of English-language audiovisual guides, which limited engagement. Recommendations include intensive English training focused on tourism vocabulary and phonetics, development of multilingual digital content, and collaboration with universities for volunteer interpreters. This research contributes theoretically to applied linguistics in tourism and practically to museum management enhancement.